Devising a systematic approach to the implementation of innovative technologies to provide the stability of transportation enterprises - Smerichevskyi, Serhii; Mykhalchenko, Oleksii; Poberezhna, Zarina; Kryvovyazyuk, Igor (Eastern-European Journal of Enterprise Technologies, 2023)
This paper reports a study of the main key components of influence on the stability of transportation enterprises in the market. A model for evaluating the effectiveness of innovation activity in the transport industry, which takes into account indicators of expenditures on innovations, has been built. It makes it possible to determine the effectiveness of introduced innovations, which indicates the appropriate level of innovation potential and the ways that the enterprise must take to increase it. The main directions of innovative development of transportation enterprises were investigated. The assessment of the economic stability of transportation enterprises in the market has established that the current state of development of enterprises is characterized by a weak level of their innovative activity. A systematic approach to the introduction of innovative technologies by a transportation enterprise in the market has been devised. This approach makes it possible to determine the required level of enterprise stability and to form a relationship between the level of innovative technologies and their stages of implementation under conditions of environmental variability. This makes it possible to increase competitive advantages, improve the efficiency of production and economic activity of enterprises. The practical implementation of the proposed model for evaluating the effectiveness of innovation activity in the transport industry has been carried out, which made it possible to allocate the most important indicators of innovation activity for the enterprise. These include specific efficiency of innovation; unit costs of innovation; innovative potential of the enterprise (defined as the proportion of own innovative developments). According to the study results, it is determined that the specific efficiency of innovations (SEI) exerts the greatest influence, which, with an increase by 1 %, provides an increase in financial stability by 1.48 %